RESPON PEMBERIAN MOL DAN TAKARAN BAHAN BAKU TERHADAP SIFAT FISIK PADA PEMBUATAN PUPUK KOMPOS PELEPAH SAWIT - Pertiwi, Nurlianti (University of Prof. Dr. Hazairin, SH, 2025)
The research aims to obtain the best type of decomposer and the composition of materials and the time needed to achieve mature fermentation in making compost. Oil palm plants grow well on podzolic soil, but high levels of fertilization are needed to overcome the poor nutrients in this type of soil. The return of organic fertilizer from palm fruit frounds waste after it has been treated with added nutrients from broiler chicken waste and then fermented with MOL is expected to be able to meet the nutrient needs of oil palm plants. The research was carried out in the Babatan sub-district, Sukaraja district, Seluma regency from December 2023 to February 2024. The research consisted of 2 factors, namely the type of decomposer and the composition of the dough material. The non-control treatment was the application of anorganic fertilizer given to all treatment combinations The control treatment was the combination of treatments without the application of anorganic fertilizer. The research observed the physical properties of compost fertilizer which included the number of fungi, color, aroma, temperature, humidity. The results of the research concluded that the control fermentation treatment took place more quickly, namely the dough matured within 8 days after fermentation, while the non-control treatment matured up to 42 days. EM-4 factory treatments produced more fungi than mol from maja fruit and golden snails. In the non-control treatment, the composition of the mixture was 1:1, showing a greater number of fungi, The color of the compost is yellowish brown with a darker color, while in the control treatment the best composition is 1:2 with a lighter color.